Corporeal Spaces in L. S. Černiauskaitė’s “The Jasmin Chamber” - Skikaitė, Izabelė (Semiotika, 2024)
The description of space in Greimas’ classical semiotics is based either on the subject’s narrative program and its relationship with the object of value or on the plastic properties of space, which determine the actor’s way of moving. In both cases, the relationship with space depends on the moving body; however, in literary texts, not only is motion important, but also the perception of space and the feelings it evokes. Usually, in literary criticism, the emotional relationship with space is regarded as a mental representation of the character. The analysis of Laura Sintija Černiauskaitė’s novelette “The Jasmin Chamber” highlights the limitations of this perspective, which assumes a one-sided link between the body and space. In the text, the character establishes a reciprocal bond with the home space. The home possesses corporeal properties, appears active and inviting, and the character functions as a sensitive and responsive body. In the novelette, a homology exists between the architectural structure and the individual body, both of which share the same category: continuous / discontinuous. The analysis of space shows that the characters connect only with family, driven by an unconscious desire for lasting relationships and continuity in their living space. Different characters’ interactions with space uncover the duality of desire: the wish to possess an object of value is intertwined with an unconscious pursuit of intense experiences.